A comparison of the safety and effectiveness of prasugrel and clopidogrel in younger population undergoing percutaneous coronary intervention: A retrospective study using a Japanese claims database. Issue 3 (March 2021) - Hagiwara, Hiromi; Fukuta, Hidekatsu; Hashimoto, Hiroya; Niimura, Takahiro; Zamami, Yoshito; Ishizawa, Keisuke; Kamiya, Takeshi; Ohte, Nobuyuki
Highlights: This study compared the safety and efficacy of prasugrel and clopidogrel. We analyzed a large claims database constructed at post-marketing stages in Japan. Comparable safety and efficacy of the two drugs was observed. Abstract: Background: Prasugrel inhibits platelet aggregation more potently than clopidogrel. In the global phase III trial, prasugrel [loading dose/maintenance dose (LD/MD), 60/10 mg] reduced the incidence of ischemic events but involved a higher risk of hemorrhage than clopidogrel in patients with acute coronary syndromes who were scheduled to undergo percutaneous coronary intervention (PCI). In the Japanese phase III trial for similar patients wherein the prasugrel dose regimen was adjusted (LD/MD, 20/3.75 mg), the efficacy of prasugrel and clopidogrel were comparable to that in the global trial; however, the safety could not be determined due to limited power. Given the strict enrollment criteria, the results of the Japanese phase III trial may not be applicable to routine clinical practice. We compared the safety and effectiveness of prasugrel and clopidogrel in the real-world setting in Japanese patients. Methods: With an analysis of a large claims database prepared during the post-marketing stages in Japan, we identified patients undergoing PCI and compared the incidence of bleeding and ischemic coronary events between patients who received prasugrel and those receiving clopidogrel. Results: Between January 1, 2014 and December 31, 2018, we identified 1977 patients who were scheduled to undergo urgent PCI (urgent PCI cohort) and 1922 who were scheduled to undergo elective PCI (elective PCI cohort). After propensity-score matching, there were no significant differences in the baseline clinical characteristics of the prasugrel and clopidogrel groups in the urgent (n = 1080) and elective PCI (n = 1626) cohorts. In Cox proportional hazard analyses, there were no significant differences in the incidence of bleeding or ischemic coronary events during the median 8-month follow-up in both cohorts. Conclusions: The safety and effectiveness of prasugrel was comparable to that of clopidogrel in real-world Japanese patients scheduled to undergo PCI.